Diagnosis and outcome of acute respiratory failure in immunocompromised patients after bronchoscopy. Issue 1 (25th July 2019) - Bauer, Philippe R.; Chevret, Sylvie; Yadav, Hemang; Mehta, Sangeeta; Pickkers, Peter; Bukan, Ramin B.; Rello, Jordi; van de Louw, Andry; Klouche, Kada; Meert, Anne-Pascale; Martin-Loeches, Ignacio; Marsh, Brian; et al.
Objective: We wished to explore the use, diagnostic capability and outcomes of bronchoscopy added to noninvasive testing in immunocompromised patients. In this setting, an inability to identify the cause of acute hypoxaemic respiratory failure is associated with worse outcome. Every effort should be made to obtain a diagnosis, either with noninvasive testing alone or combined with bronchoscopy. However, our understanding of the risks and benefits of bronchoscopy remains uncertain. Patients and methods: This was a pre-planned secondary analysis of Efraim, a prospective, multinational, observational study of 1611 immunocompromised patients with acute respiratory failure admitted to the intensive care unit (ICU). We compared patients with noninvasive testing only to those who had also received bronchoscopy by bivariate analysis and after propensity score matching. Results: Bronchoscopy was performed in 618 (39%) patients who were more likely to have haematological malignancy and a higher severity of illness score. Bronchoscopy alone achieved a diagnosis in 165 patients (27% adjusted diagnostic yield). Bronchoscopy resulted in a management change in 236 patients (38% therapeutic yield). Bronchoscopy was associated with worsening of respiratory status in 69 (11%) patients. Bronchoscopy was associated with higher ICU (40% versus 28%; p<0.0001) and hospital mortality (49% versus 41%; p=0.003). The overall rate of undiagnosed causes was 13%. After propensity score matching, bronchoscopy remained associated with increased risk of hospital mortality (OR 1.41, 95% CI 1.08–1.81). Conclusions: Bronchoscopy was associated with improved diagnosis and changes in management, but also increased hospital mortality. Balancing risk and benefit in individualised cases should be investigated further. In a pre-planned analysis of immunocompromised critically ill patients with acute respiratory failure, bronchoscopy was associated with better diagnosis and management but worse outcome. The decision to perform bronchoscopy should be individualised. http://bit.ly/2Dusahh